OCCURRENCE AND BACTERIAL CYCLING OF D AMINO ACID ISOMERS IN AN ESTUARINE ENVIRONMENT - Jørgensen N.O.G.; Middelboe M. (My University, 2006)
Abundance of d isomers of amino acids has been used in studies of organic matter diagenesis to determine the contribution of bacterial biomass to the organic matter, especially in marine sediments. However, fluxes of d amino acids in pelagic waters are poorly known. Here we present seasonal changes (March–September) in concentrations of dominant d amino acids in the pool of dissolved free and combined (hydrolysable) amino acids (DFAA and DCAA) in the shallow Roskilde Fjord, Denmark. The amino acid dynamics are related to pelagic bacterial density and activity and abundance of viruses. d␣isomers made up 3.6 and 7.9% of the DFAA and DCAA (average values), respectively, and had similar seasonal variations in concentrations. In batch cultures (0.7- and 0.2-m filtered water in a 1:9 mixture) microbial activity reduced l+d DCAA concentrations in seven of ten sampling dates, while DCAA were released at the remaining three sampling times. NH 4 + balance (uptake or release) in the cultures correlated significantly with variations in concentrations of d-DCAA, but not with the total DCAA pools. Abundance of viruses did not correlate with density or production of bacteria in the fjord, but covaried with mineralization of total C, DCAA and PO 4 3− in the batch cultures. The content of d amino acids in bacterial biomass in the cultures varied from 6.7 to 12.5% and correlated with the d isomer concentration in the fjord, except for d-Ala. In an additional six-day batch culture study, DCAA and d-DCAA were assimilated by the bacteria during the initial 36 h, but were released between 36 and 42 h simultaneous with a decline in the bacterial density. Our results demonstrate that peptidoglycan components contribute to natural amino acid pools and are assimilated by bacterial assemblages. This cell wall “cannibalism” ensures an efficient recycling of nutrients within the microbial community. Significant positive correlations between viral abundance and bacterial mineralization of organic matter in the fjord indicated that viral lysis contributed to this nutrient recycling.
Keywords: DFAA; DCAA; D ISOMERS; BACTERIA; VIRUS; N CYCLING